2015
DOI: 10.1159/000437365
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Is Associated with a Favorable Outcome in Diabetic Patients with Cervical Lymph Node Metastasis of Differentiated Thyroid Cancer

Abstract: years) was associated with longer DFS than the nonmetformin subgroup (8.6 years) (HR 0.16, p = 0.021); metformin treatment was also associated with longer DFS in this subgroup in multivariate analysis after adjusting age, BMI, duration of diabetes, presence of tumor at resection margin, and serum thyroglobulin level at ablation (HR 0.03, p = 0.035). Conclusions: Metformin treatment is associated with low recurrence in diabetic patients with cervical LN metastasis of DTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 28 publications
0
26
1
Order By: Relevance
“…Recent studies suggest that metformin treatment could reduce tumor cell invasion in pancreatic cancer [35]. Metformin treatment of diabetetic patients is associated with low recurrence of cervical lymph node metastasis of differentiated thyroid cancer [36]. Indeed, we found that FN protein abundance was higher in thyroid tumors of HFD- Thrb PV/PV Pten +/− mice than in LFD- Thrb PV/PV Pten +/− mice (Figure 4B-I, panel a, lanes 4-6 versus lanes 1-3; quantitative data: Figure 4B-II-a, bar 3 versus bar 1).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies suggest that metformin treatment could reduce tumor cell invasion in pancreatic cancer [35]. Metformin treatment of diabetetic patients is associated with low recurrence of cervical lymph node metastasis of differentiated thyroid cancer [36]. Indeed, we found that FN protein abundance was higher in thyroid tumors of HFD- Thrb PV/PV Pten +/− mice than in LFD- Thrb PV/PV Pten +/− mice (Figure 4B-I, panel a, lanes 4-6 versus lanes 1-3; quantitative data: Figure 4B-II-a, bar 3 versus bar 1).…”
Section: Resultsmentioning
confidence: 99%
“…Despite recent research suggesting an improved survival associated with the use of anti-diabetic medications, their use as adjuvant therapy in patients undergoing surgery for pancreatic cancer remains unclear. [21][22][23] Using a large, nationally representative sample of patients, the current study sought to investigate the impact of metformin use on OS among patients who had undergone Fig. 1 Kaplan-Meier curves of metformin users vs. non-users surgical resection of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Besides lowering the thyroid cancer risk, metformin treatment has been associated with longer disease-free survival in T2DM patients with cervical lymph node metastasis of DTC (Jang et al 2015). In a retrospective study involving 240 DTC individuals, diabetic patients who were treated with metformin had smaller thyroid cancer size, higher complete response rate and longer progression-free survival in comparison to nonmetformin-treated diabetic patients and non-diabetic thyroid cancer patients matched by age, gender and BMI (Klubo-Gwiezdzinska et al 2013).…”
Section: Differentiated Thyroid Cancer (Dtc) Epidemiologymentioning
confidence: 99%